Exogenous giberellic acid stimulates bulb dormancy breaking and the role of paclobutrazol in maintaining the size of harvested bulb of lily (Lilium sp.) cv. tisento - Siti Nur Anisah,; Ratnadewi, Diah; Supena, Ence Darmo Jaya (Penerbit Universiti Kebangsaan Malaysia, 2023)
Lilies are increasingly demanded in Indonesia. However, the production of lily seedlings in Indonesia still needs to be improved, causing a strong dependence on imported bulbs as the planting material and low competitiveness in foreign flower markets. Insufficient lily production is due to the decreasing quality of the bulb as the planting material and the time required for vernalization to break the bulb dormancy. The study aimed to accelerate the time of bulb dormancy breaking and maintain the size of the lily bulb to get an efficient flower production with good quality. The research was conducted in a greenhouse during the rainy and dry seasons. Various exogenous gibberellic acid (GA3) concentrations with different soaking times were applied to lily bulbs to shorten the dormancy period. The most efficient treatment was soaking the bulbs in 100 mg/L of GA3 for 16 hours, from 19-20 weeks to 12-13 weeks. Further, paclobutrazol (PBZ) was sprayed on the plants to decelerate vegetative growth and grow bulb size. The results showed that GA3 could partly substitute vernalization to break bulb dormancy, and PBZ maintained the bulb size after plant harvesting. Additionally, the plant height was suppressed, and the stem diameter, leaf chlorophyll, and bulb carbohydrate content were significantly increased under 300 mg/L PBZ treatment, resulting in the bulbs’ bigger size.